Hypoglycemic Activity of Endotoxin II. Mechanism of the Phenomenon in BCG-infected Mice - Shands, J. W. (1969)
The mechanism of the hypoglycemic activity of endotoxin in hyperreactive BCG mice was investigated. The mechanism was found to be an inhibition of the synthesis of glucose from noncarbohydrate sources. The possibilities of an induced hypermetabolic state and an induced release of insulin in response to endotoxin as causes for the hypoglycemic response were essentially ruled out. In addition, no clear-cut evidence of an insulin-like action by endotoxin was found in the in vivo setting.